Dziedzictwo kulturowe wspólnot lokalnych w tradycji ustnej - Tadeusz Paleczny (Ksiegarnia Akademicka Publishing, 2020)
Cultural Heritage of Local Communities in Oral History. The Base of Constructing the Social Memory